2016
DOI: 10.18632/oncotarget.7010
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 or miR-145 overexpression increases cetuximab-mediated antibody-dependent cellular cytotoxicity in human colon cancer cells

Abstract: miR-143 and miR-145 are downregulated in colon cancer. Here, we tested the effect of restoring these miRNAs on sensitization to cetuximab in mutant KRAS (HCT116 and SW480) and wild-type KRAS (SW48) colon cancer cells. We evaluated cetuximab-mediated antibody-dependent cellular cytotoxicity (ADCC) and the modulation of signaling pathways involved in immune effector cell-mediated elimination of cancer cells. Stable miR-143 or miR-145 overexpression increased cell sensitivity to cetuximab, resulting in a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 71 publications
4
40
0
Order By: Relevance
“…The expression of miR-17 and miR-146 was downregulated, while the expression of miR-145 was upregulated. This is consistent with the role of these miRNAs in cancer development—the overexpression of miR-17 and mir-146 is a feature of hyper-proliferating cancer cells [20,59], while the enhanced expression of miR-145 impairs proliferation of the HCT116 colon cancer cell line [60]. …”
Section: Discussionsupporting
confidence: 78%
“…The expression of miR-17 and miR-146 was downregulated, while the expression of miR-145 was upregulated. This is consistent with the role of these miRNAs in cancer development—the overexpression of miR-17 and mir-146 is a feature of hyper-proliferating cancer cells [20,59], while the enhanced expression of miR-145 impairs proliferation of the HCT116 colon cancer cell line [60]. …”
Section: Discussionsupporting
confidence: 78%
“…Silencing of KRAS mRNAs using siRNA [124, 125] or miRNAs (such as Let-7 [126] or miR143 [127]), which indirectly suppress levels of mutated KRAS proteins in cancer cells. A new administration method was developed to maintain siRNA stability and to introduce siRNA slowly into KRAS G12D -mutated pancreatic carcinoma tissue [125].…”
Section: Timeline View: the “Oncogene Theory ” The Discovery Of Viramentioning
confidence: 99%
“…The repression of these miRNAs suggest a specific growth promoting overall effect of FA on the malignant cells in our study, because ectopic expression of miR‐1, miR‐126, miR‐139 and miR‐34a was shown to suppress the proliferation of colon and other cancer cells . Furthermore, the ectopic expression of miR‐143 restores the responsiveness of colon cancer cells for the anti‐EGFR antibody cetuximab, which is therapeutically used as anti‐cancer drug .…”
Section: Discussionmentioning
confidence: 52%